A new record of Aretes indicus (Coutiere 1903)(Alpheidae: Caridea) from northern Arabian Sea - Farhana Shafiq Ghory (International Academy of Ecology and Environmental Sciences, 2021)
The alpheid shrimp, Aretes indicus Coutiere, 1903 is reported for the first time at the northern Arabian Sea. The species is known to have a symbiotic relationship with the rock boring intertidal dwelling sea urchins. The present shrimps were found in an old undated sample which contained sea urchin Echinometra mathaei. Apparently the shrimp was dislodged while transferring the sample from coast to the lab and during handling in preservation.